6th Annual Fresno County Young Lawyers Association Justice Hopper Memorial Luncheon; Speaker: San Francisco Superior Court Judge Ira Brown - Watkins, Howard::::::::: (1987)
Justice Donald Franson, Judge Ira Brown and Fresno County Bar Association Vice-President Herbert Levy